Faktor-Faktor yang berhubungan dengan Kejadian Stunting pada Balita Usia 24-59 Bulan dari Keluarga Petani di Wilayah Kerja Puskesmas Gunung Labu Kabupaten Kerinci - Asparian Asparian; Enda Setiana; Evy Wisudariani (Universitas Baiturrahim, 2020)
Background : Stunting is a state of height index according to age under -2 SD according to WHO standards. Nutrition problems in farmers can occur due to poverty which is the root of nutrition problems. The purpose of this study was to determine the factors associated with the incidence of stunting in children aged 24-59 months from farming families in the Gunung Labu Primary Health Care in Kerinci Regency. Method :The design of this study was cross sectional. The total population in this study was 1,422 toddlers, while the sample in this study was 98 toddlers from farming families. Analysis used the Chi-Square test and Multiple Logistic Regression. Result :This study found the prevalence of stunting in infants 32.34%. Factors related to the incidence of stunting in infants were household level food security and mother's education level. The most dominant factor related to the incidence of stunting in infants was household-level food security (OR = 4,722; 95% CI = 1,599-13,941). Households ware encouraged to use home yards as a place to meet food needs and provide a variety of foods and balanced nutrition for infants so that nutritional needs can be met.